Scandal in Skibbereen - Connolly, Sheila (Connolly, Sheila. County Cork mysteries., 2014)
Bostonian Maura is beginning to feel settled in her new Irish home, just in time for summer tourist season to bring fresh business to her pub. But the first traveler to arrive is thirsty for more than just a pint of Guinness. Althea Melville is hot on the trail of a long-lost Van Dyck painting. Maura agrees to help Althea meet with the residents at the local manor house, the most likely location of the missing art. But when the manor's gardener is found murdered, Maura wonders what Althea's real motives are. Now, to solve the secret of the lost portrait and catch a killer, Maura will have to practice her Irish gift of gab and hunt down some local history before someone else is out of the picture.